THU0544 Preclinical Drug Testing in Ex Vivo 3-D Dynamic Culture in Erdheim-Chester Disease. (10th June 2014) - Biavasco, R.; Belloni, D.; Doglioni, C.; Dagna, L.; Ferrero, E.; Ferrarini, M.
Abstract : Background: Erdheim-Chester disease (ECD) is a non-Langerhans cell histiocytosis of unknown etiology and poor prognosis. The disease is characterized by the accumulation of foamy CD68+ histiocytes in bones and soft tissues, leading to the development of protean clinical manifestations (1, 2). Two distinct but possibly interconnected pathogenic events have been described: an uncontrolled chronic inflammation inside the lesions (3) and the occurrence of an oncogenic BRAF V600E mutation in histiocytes (4). Interferon-a is considered the first line therapy for ECD, but its efficacy varies according to sites of disease involvement. Alternative therapeutic approaches, based on cytokine- (anakinra, infliximab, tocilizumab) (5) or BRAF V600E - (vemurafenib) targeting are currently under investigation. The assessment of drug efficacy in ECD, however, is hampered by both the extreme rarity of the disease, and the lack of suitable in vitro or in vivo models. 3-D tissue culture systems are emerging as an invaluable tool for drug testing. In particular, the Rotary cell culture system (RCCS™) bioreactor allows for 3-D dynamic culture of samples by optimizing mass and gas transfer. Indeed, we have recently validated the system for long-term (up to 15 days) culture of normal and pathological human tissues, showing the maintenance of viability and histo-architecture of cultured biopsies, as well as the feasibility to assess the impact of drugs (6). Objectives: The aim of the study was to set up a preclinical model for drug testing for ECD, taking advantage of a 3-D dynamic culture of ex vivo biopsies in the RCCS™ bioreactor. Methods: To assess and compare the efficacy of vemurafenib, infliximab and tocilizumab on ECD lesions, we obtained 4 contiguous tissue fragments from ECD biopsies and kept them in parallel cultures in bioreactor in the presence of each drug. We then evaluated the release of pro-inflammatory cytokines, metalloproteinases and necrosis markers through Bio-Plex Multiple-Cytokine Assays, zymography and G6PD determination in 48-hrs culture supernatants. Results: As compared to the untreated sample, infliximab treatment determined a marked decrease in cytokine release and an anti-parallel increase of necrosis markers, supporting apoptosis induction in histiocytes. Tocilizumab induced massive mobilization of macrophages from the biopsy into the supernatant, but no cellular toxicity. The effects of vemurafenib were instead unremarkable, possibly due to the negligible fraction of BRAF-mutated histiocytes inside the lesions. Conclusions: The RCCS™ bioreactor system is a well-suited tool for preclinical drug testing in ECD and allows both to compare the efficacy of drugs and to recapitulate their in situ mechanisms of action. This system can be further exploited as a tool to predict the impact of different therapeutic approaches in individual ECD patients. References: Haroche et al, Rheum Dis Clin North Am. 2013;39(2):299-311 Cavalli et al, Ann Rheum Dis. 2013;72(10):1691-5. Stoppacciaro et al, Arthritis Rheum. 2006;54(12):4018-22 Haroche et al, Blood. 2012;120(13):2700-3. Dagna et al, J Clin Oncol. 2012;30(28):e286-90 Ferrarini et al, PLoS One. 2013;8(8):e71613. Acknowledgements: We thank dr Luca Genovese and dr Massimo Alfano for the invaluable help in the assessment of supernatants' cell viability. This work was supported in part by the Italian Ministry of Health (GR-2009-1594586 to LD). Disclosure of Interest: : None declared DOI: 10.1136/annrheumdis-2014-eular.4223